Evaluation of a Pilot Project to Introduce Simulation-Based Team Training to Pediatric Surgery Trauma Room Care. (14th February 2017) - Lehner, Markus; Heimberg, Ellen; Hoffmann, Florian; Heinzel, Oliver; Kirschner, Hans-Joachim; Heinrich, Martina
Abstract : Introduction . Several studies in pediatric trauma care have demonstrated substantial deficits in both prehospital and emergency department management. Methods . In February 2015 the PAEDSIM collaborative conducted a one and a half day interdisciplinary, simulation based team-training course in a simulated pediatric emergency department. 14 physicians from the medical fields of pediatric surgery, pediatric intensive care and emergency medicine, and anesthesia participated, as well as four pediatric nurses. After a theoretical introduction and familiarization with the simulator, course attendees alternately participated in six simulation scenarios and debriefings. Each scenario incorporated elements of pediatric trauma management as well as Crew Resource Management (CRM) educational objectives. Participants completed anonymous pre- and postcourse questionnaires and rated the course itself as well as their own medical qualification and knowledge of CRM. Results . Participants found the course very realistic and selected scenarios highly relevant to their daily work. They reported a feeling of improved medical and nontechnical skills as well as no uncomfortable feeling during scenarios or debriefings. Conclusion . To our knowledge this pilot-project represents the first successful implementation of a simulation-based team-training course focused on pediatric trauma care in German-speaking countries with good acceptance.